GEJALA KESALAHAN PELAFALAN FONEM DALAM BAHASA INDONESIA PADA SISWA KELAS AWAL SEKOLAH DASAR (Studi Kasus di Kabupaten Pandeglang) - Lela nurfarida (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
Indonesian language errors in the phonological level can occur either the use of language orally or in writing. Most of the Indonesian language errors in the phonology level are related to pronunciation. Primary School is the first place to acquire a second language after the mother tongue as its first language. These conditions can affect the linguistic situation of students, especially in the early classes. Therefore, there is a high probability of error in language in this case phonology as an early part of the introduction of letters to the students. In the early grades of elementary school in Pandeglang area, especially the early classes, many people make mistakes in pronunciation of several letters of Indonesian alphabet such as phoneme / b /, / c /, / d /, / f /, / v /, / r /, / S /, / t /, / z /. The cause of the error can occur. This research was conducted by using the reading skill study method at the elementary school students in Pandeglang District. The results of the study showed that each student who was sampled for an Asses reading ability showed the same symptom of error on pronunciation of phonemes / b /, / c /, / d /, / f /, / v /, / r /, / s / , / T /, / z /. The condition is closely related to the acquisition of language performed by the environment and the ability of mastery in the mother tongue.